Immunology of tissue homeostasis, ovarian cancer growth and regression, and long lasting cancer immune prophylaxis - review of literature - Bukovsky, Antonin (Histology and histopathology, 2021)
Data on the substantial physiological role of the immune system in the organism's ability to manage proper differentiation and function of normal tissues (tissue homeostasis), and detailed causes of the immune system's essential role for the in-vivo stimulation of cancer growth, are severely lacking. This results in a lack of effective cancer immunotherapy without adverse events, and in the lack of long-lasting cancer immune prophylaxes, particularly in ovarian cancers. Elimination of blood auto-antibodies blocking anti-cancer T cell effectors by intermittent moderate doses of cyclophosphamide, facilitation of the immune system reactivity against alloantigens of cancer cells by two subsequent blood transfusions, and augmentation of anticancer immunity by weekly intradermal injections of bacterial toxins, caused during the subsequent treatment-free period, lasting for two to four weeks, regression of inoperable epithelial ovarian cancers and regeneration of the tremendously metastatically altered abdominal tissues into normal healthy conditions without multivisceral cytoreductive surgery, which can result in life-threatening consequences. An otherwise untreated rectal cancer, progressing over 3 years, regressed after severe toxic dermatitis lasting over one week. This was caused by an accidental consumption of a large raw shiitake mushroom. Subsequent daily consumptions of 2 g Metformin ER and honeybee propolis ethanol extract, and weekly single larger raw shiitake mushroom, which all stimulate immune system reactivity against cancer stem cells, prevented malignant recurrence over the next 29 years without recurring dermatitis, and maintained healthy organism's conditions. These observations indicate that regression of advanced inoperable cancers and long-lasting cancer immune prophylaxis can be reached by simple approaches.
Keywords: Carcinoma, Ovarian Epithelial; Cell Proliferation; Humans; lidé středního věku; lokální recidiva nádoru; metformin; Metformin; Middle Aged; zvířata; nádory vaječníků; propolis; Homeostasis; houby šii-take; imunitní systém; nádory rekta; Immune System; proliferace buněk; Neoplasm Recurrence, Local; Autoantibodies; Shiitake Mushrooms; T-Lymphocytes; výsledek terapie; epiteliální ovariální karcinom; včely; Treatment Outcome; imunoterapie; autoprotilátky; ženské pohlaví; Propolis; T-lymfocyty; Animals; Ovarian Neoplasms; lidé; Rectal Neoplasms; Bees; homeostáza; Immunotherapy; Female